2019
DOI: 10.1073/pnas.1906766116
|View full text |Cite
|
Sign up to set email alerts
|

Classifying fishing behavioral diversity using high-frequency movement data

Abstract: Effective management of social-ecological systems (SESs) requires an understanding of human behavior. In many SESs, there are hundreds of agents or more interacting with governance and regulatory institutions, driving management outcomes through collective behavior. Agents in these systems often display consistent behavioral characteristics over time that can help reduce the dimensionality of SES data by enabling the assignment of types. Typologies of resource-user behavior both enrich our knowledge of user cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Our feature selection method, however, retains readability and interpretability as it preserves the original variable values in a reduced space. As noted by Jain and Dubes (1988), "validation of clustering structures is the most difficult and frustrating part of cluster analysis, " but is necessary for ensuring the clusters accurately reflect the "real-world" data (O'Farrell et al, 2019). We note that suitable computational internal validation methods are available in the machine learning literature but have been given only a fraction of attention in métier analysis.…”
Section: Discussion a Robust Framework For Clustering Commercial Fishmentioning
confidence: 93%
See 3 more Smart Citations
“…Our feature selection method, however, retains readability and interpretability as it preserves the original variable values in a reduced space. As noted by Jain and Dubes (1988), "validation of clustering structures is the most difficult and frustrating part of cluster analysis, " but is necessary for ensuring the clusters accurately reflect the "real-world" data (O'Farrell et al, 2019). We note that suitable computational internal validation methods are available in the machine learning literature but have been given only a fraction of attention in métier analysis.…”
Section: Discussion a Robust Framework For Clustering Commercial Fishmentioning
confidence: 93%
“…Effective fisheries management requires an understanding of human behavior (Hilborn, 2007;Davie and Lordan, 2011;Fulton et al, 2011;O'Farrell et al, 2019). Evidence has shown that when this is ignored it can lead to unexpected and undesirable outcomes from management decisionmaking (Fulton et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, historical data from digitized texts, photographs, or ship logs can provide insights into the distribution or abundance of species at times when scientific sampling data are limited [ 51 ]. Culturomics can shed light on the behavior and preferences of fishers [ 52 ], for example, by assessing regional characteristics of recreational fisheries based on YouTube videos or discussion forums ( Fig 1A ) [ 7 , 9 , 12 ] or by analyzing internet search frequency to explore global trends in fishing interest and seasonality [ 5 ]. These approaches can also be used to monitor the effectiveness of fisheries management initiatives by tracking attitudes and compliance of fishers before, during, and after implementation of regulations and to anticipate reactions.…”
Section: Introductionmentioning
confidence: 99%